God, the Christ and the Spirit in William P. Young"s bestseller The shack seen from a Pauline and Johannine perspective - Aarde, Andries van (HTS teologiese studies, 2009)
Among its more than a million readers, The shack has empowered traditionalists and seekers among Christian spirituals but has also been condemned for patripassionism and modalism. This article consists mainly of two sections. The first section considers the issue of reviewers of The shack often assessing its religious legitimacy and the value of its message by means of critically questioning its adherence to texts in the Christian Bible. The second section focuses on the accusation that, dogmatically seen, The shack’s narrative point of view is heresy, especially because of its nonstandard view of Christian dogma with regard to God Triune. The aim of the article is to argue that a great deal of commonality exists between the author of The shack and both Pauline and Johannine mysticism. With regard to their God talk, the author and these biblical writers express more of a present immanent communion with the transcendental God than an expectancy of authenticity that still lies in the future and exists outside humankind’s immanent time and space. It is as if they draw the end time into the sphere of the here and now by passionately talking about communion with God as a process of the future, inhaled by the present. By doing so, the God-threesome meet wounded humankind in a ‘shack’, not in the ‘church’ as such or ‘Scripture’ as such as if God could be placed in a box.